A mini-review on three-electrode configuration for Solid Oxide Cells - Jing Zhu; Bin Chen; Meng Ni; Haoran Xu (Energy Reviews)
The reference electrode (RE) is a crucial tool for isolating the potential of individual electrodes, allowing for the characterization of anode and cathode performance and enabling real-time monitoring of cell electrode conditions. However, integrating a three-electrode configuration, which includes an RE, into solid oxide cells presents challenges due to their high operating temperature and all-solid-state structure. Thus, this paper reviews the three-electrode configuration for solid oxide cell characterization. It starts with an introduction to the principles of polarization and electrochemical impedance spectroscopy (EIS) measurements in three-electrode experiments, providing guidance for cell structure design and experiment set. The impacts of RE material properties, size and surrounding atmosphere on potential accuracy are discussed. Additionally, the positions of RE, cell structures, and applications in both electrolyte-supported and electrode-supported cells are analyzed. Methods for validating experimental data and strategies to enhance reliability are also presented. Finally, this paper outlines prospects for further research and development in three-electrode configurations.